“Asoleado” (“Sunny”) of Cauquenes and Conception: The Rise and Fall of a Chilean Wine with Appelation of Origin [Asoleado de Cauquenes y Concepción: Apogeo y Decadencia de Un Vino Chileno Con Denominación de Origen] - Lacoste, P; Cofre-Silva, C (Universidad de Tarapaca, 2016)
The “asoleado” (sunny) of Cauquenes and Concepcion represents a case of particular interest among the typical wines of Latinamerica. In the nineteenth century it was the best wine in Chile according to market preferences. In the following century, was recognized by the State in 1953 as the first wine with Appellation of Origin in the country, next to pajarete and sweet wine Elqui. With this background, sunny had high development prospects in domestic and international markets. However, these expectations were frustrated and product, at present, has no relevance in the Chilean wine industry. This article examines the boom cycle of the product through the press of the time (1850-1880), and provides some reasons for his subsequent decline. © 2016, Universidad de Tarapaca. All rights reserved.